A study on the longevity of fixed partial dentures done by senior clinicians of UPCD from 1990-1998 - Canlas, Miamor A.; Adarve, Ranier M. (Adviser).
Fixed partial denture (FPD) restoration involves a tedious work of treatment planning, tooth preparation and laboratory. It may involve healthy abutment tooth that may be compromised. FPD work is also costly. The most often inquiry not only of dentist but of patients as well is the number of years the restoration will serve. The aim of this study is to analyze the survival rate of FPDs done in the University of the Philippines College of Dentistry to determine its mean survival rate and to point out the causes of its failures. The data gathered paves the way for the improvement of longevity and prevention of failure. Results showed a mean survival time of 6.75 years for acrylic crowns and 5.33 for bridges. Porcelain Fused to Metal bridges has a mean survival time of 4.3 years. The most common cause of failure was retention problem followed by fractured retainer, defective margins and caries, pulpal pathology, wear, poor esthetics; in the order of frequency. Recall is essential for the prevention of these failures and to prolong its length of service.
Seminar Paper--Doctor of Dental Medicine--University of Philippines Manila.
Keywords: Denture, Partial, Fixed